Change Of Social Capital Of Dairy Farmers Groups: A Case Study Of Institutionalization Of Sapi Merapi Sejahtera Sleman (Samesta) Cooperative In Sleman, Yogyakarta - Najmudin Najmudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
The results shows that there are changes of social capital of dairy farmers groups in the process of institutionalization of SAMESTA cooperatives. The change is the impact of the conditions of Indonesian dairy. These changes occur in several elements of social capital, as follows: (1) Value, as a guide and reinforcement of farmers’ positive behavior. The existing values among farmers are klangenan (like), titen (scrutinize deeply), honesty, and togetherness. These values ​​become the fuel that forces the farmers to relate each other and realize the more transparent and fairer cooperative. This case shows the influence of cultural values ​​on the farmers’ economic behavior. They calculate inputs and outputs, and make some adjustments to prevent them from losing and calculate the standard number of cows that they have. (2) Trust changes positively, especially by raising the milk price from farmers, although it gives a risk to the cooperative income. This decision is expected to increase the farmers' ethos, thus impacts on the increase of milk production. (3) Networks, in which the relationship between farmers firstly occurs in hamlet area, then it extends the network beyond those limits. Farmers from different villages are connected naturally. This inter-subject's relationship occurs due to the same goals, which are wishes to be more dignified, prosperous, and get fair treatment.